The Influence of Emotional and Spiritual Intelligence on Lecturer Performance Through Organisational Citizenship Behaviour in Private Universities - Mochamad Vrans Romi (Khazanah Sosial, 2024)
This study aims to explore the influence of emotional and spiritual intelligence on lecturer performance, with organisational citizenship behaviour (OCB) acting as a mediating variable. The research focuses on lecturers at private universities in Bandung City, where performance is critical to institutional success in a competitive educational landscape. The study employs a quantitative explanatory survey design, utilising data from 371 respondents, all permanent lecturers at private universities in Bandung. Data was collected through structured questionnaires and analysed using the Structural Equation Model (SEM) via the AMOS application. This model allowed for the measurement of both direct and indirect effects of emotional and spiritual intelligence on performance, with OCB as the mediator. The results show that both emotional and spiritual intelligence have significant direct and indirect effects on lecturer performance. Emotional intelligence directly improves performance and also contributes to increased OCB, which further enhances performance. Similarly, spiritual intelligence is a strong predictor of lecturer performance, and its positive impact is amplified through the mediating role of OCB. The study highlights the importance of emotional and spiritual dimensions in fostering positive citizenship behaviours, which, in turn, enhance lecturer effectiveness and institutional success. The findings suggest that educational institutions should prioritise the development of emotional and spiritual intelligence alongside technical skills in lecturer training programmes. By fostering a supportive work environment through OCB, institutions can improve lecturer performance and, ultimately, the quality of education provided to students. This study provides a comprehensive model integrating emotional intelligence, spiritual intelligence, OCB, and performance in the context of higher education, offering valuable insights into the role of personal and organisational factors in lecturer effectiveness.